I'dadu al-Mu'allim wa Tanmiyatuhu Mihniyyan fi Dhaui al-Ittijahat al-Mu'ashirah - Syakur, Naema al-Mahdi Abu (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2024)
The landscape of education is continually evolving, shaped by contemporary trends that demand a dynamic and adaptive approach to teacher preparation and professional development. This abstract delves into the critical intersection of